Web-Based Attendance System For Daily Freelance Workers At The Secretariat Of The Regional House Of Representatives (DPRD) Of Minahasa Regency Using The Prototype Method - Rawung, Lanamey Praisy Indiana; Rorimpandey, Gladly Caren (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The procedure of recording the attendance of casual workers at the Secretariat of the Regional People's Representative Council (DPRD) of Minahasa Regency is still carried out manually, which is easily exposed to recording errors, manipulation of data, and requires ineffective time and energy. To solve this problem, this research aims to design and develop a web-based attendance recording system by applying the Prototype method. This method was chosen because it supports the development of a system that is interactive and responsive to user needs through a series of iterations between developers and users. The designed system enables electronic attendance recording, employee data management, as well as the presentation of attendance reports automatically and precisely. The pilot test shows that the system is able to increase efficiency and accuracy in the attendance administration process, as well as facilitate supervision by the authorities. Therefore, the system is expected to serve as an effective solution to support a more modern and transparent administrative management within the Secretariat of Minahasa Regency Parliament.